The possible onset of fibromyalgia following acute COVID-19 infection - Savin, Einat; Rosenn, Gali; Tsur, Avishai M.; Hen, Or; Ehrenberg, Scott; Gendelman, Omer; Buskila, Dan; Halpert, Gilad; Amital, Daniela; Amital, Howard (PLOS ONE, 2023)
Introduction The exact pathogenesis of fibromyalgia (FM) syndrome is unclear. However, various infectious have been implicated with the development of FM after their acute phase. We aimed to investigate the incidence of FM syndrome among convalesced individuals following hospitalization for Acute Coronavirus Disease-2019 (COVID-19). Methods We performed a cross-sectional study on patients who were discharged after COVID-19 hospitalization from the Sheba Medical Center, Israel, between July 2020 to November 2020. A phone interview was performed consisting of the following questionnaires: the Fibromyalgia Survey Diagnostic Criteria Questionnaire, Sense of Coherence Questionnaire to evaluate resilience, and the Subjective Traumatic Outlook Questionnaire to assess the associated psychological aspects of the trauma. The incidence of post-COVID FM was calculated and regression models were performed to identify predictors. Results The study population consisted of 198 eligible patients who completed the phone interview. The median age was 64 (52–72) and 37% were women. The median follow-up was 5.2 months (IQR 4.4–5.8). The incidence of FM was 15% (30 patients) and 87% (172 patients) had at least one FM-related symptom. Female gender was significantly associated with post-COVID FM (OR 3.65, p = 0.002). In addition, high median Subjective Traumatic Outlook scores and low median Sense of Coherence scores were both significantly associated with post-COVID FM (OR 1.19, p<0.001 and OR 0.92, p<0.001, respectively). Conclusions FM is highly prevalent among COVID-19 convalescent patients. Our finding suggests that a significant subjective traumatic experience and a low resilience are highly associated with post-COVID FM.